The Effect of the Online and Offline Blended Teaching Mode on English as a Foreign Language Learners’ Listening Performance in a Chinese Context - Jiang, Yuhong; Chen, Yingying; Lu, Jiasheng; Wang, Yiqing (Frontiers in Psychology, 2021)
With the rapid development of computer, multimedia, network and communication technologies, all walks of life are undergoing change and development driven by “Internet Plus”. Especially due to the COVID-19 outbreak, domestic English listening learning methods have undergone revolutionary changes. The online courses and materials become the norm for students, combined with the offline English listening learning activities, and finally formed an online and offline blended learning mode. The purpose of this study is to explore the effect of online and offline blended mode and its impact on students’ learning outcomes, learning attitudes, learning interest, and learning strategies in English listening. A three-month teaching experiment of online and offline blended learning mode is conducted in English listening teaching. Adopting a combination method of qualitative and quantitative research, this study examines two classes of students’ engagement process and obtains results from analyzing their English listening tests and in-depth interviews. The findings suggest that the online and offline blended learning mode is conducive to enhancing students’ listening comprehension ability. Moreover, students’ attitudes towards English listening shift from a relatively negative engagement into a more positive one. Meanwhile, students’ learning interest in English listening gains development, and learning strategies of English listening become more diversified.